2018
DOI: 10.1007/s00167-018-5268-9
|View full text |Cite
|
Sign up to set email alerts
|

Midbody of the medial meniscus as a reference of preservation in partial meniscectomy for complete discoid lateral meniscus

Abstract: Purpose To evaluate the postoperative size of discoid lateral meniscus using magnetic resonance imaging (MRI) after partial meniscectomy relative to the size of medial meniscus midbody. Methods This study included 48 patients who underwent arthroscopic partial meniscectomy with or without repair for symptomatic complete discoid meniscus. The intraoperative size of midbody of medial meniscus was used as a reference for partial meniscectomy. MRIs were performed pre‐ and postoperatively. Quantitative evaluations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Thus, there remains no clear consensus regarding the extent of peripheral rim preservation and what anatomic reference should be considered during arthroscopic partial meniscectomy. Recently, Kim et al [37] suggested that the midbody of the medial meniscus should be considered the reference point for the remaining peripheral rim in partial meniscectomy for patients with complete DLM; this is identical to our practice regarding the reference (Fig. 3).…”
Section: Surgical Treatmentsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, there remains no clear consensus regarding the extent of peripheral rim preservation and what anatomic reference should be considered during arthroscopic partial meniscectomy. Recently, Kim et al [37] suggested that the midbody of the medial meniscus should be considered the reference point for the remaining peripheral rim in partial meniscectomy for patients with complete DLM; this is identical to our practice regarding the reference (Fig. 3).…”
Section: Surgical Treatmentsupporting
confidence: 62%
“…Recent studies showed that the condylar cut‐off sign on tunnel‐view radiography has a high specificity, indicating its diagnostic utility for complete DLM in children and adolescents [26, 27, 52]. In addition, Kim et al [37] reported a significant association between meniscal tear of the contralateral knee and the presence of one or more than two indirect signs on plain radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical studies have shown that surgical treatment is the best therapy for discoid meniscus, as conservative medical treatment has no obvious effect (8). In the past, open surgery was the only solution to improve the shape and function of the meniscus.…”
Section: Discussionmentioning
confidence: 99%
“…At present, arthroscopic surgery is the primary method for treating symptomatic DLM, which mainly includes partial meniscectomy, partial meniscectomy and suture/ repair Figure 3, subtotal or total meniscectomy, and meniscal allograft transplantation. 1,132 Although there are some differences in the description of the partial meniscectomy of DLM in different literature, such as saucerization, meniscoplasty, or reshaping, all of them resect the redundant central region, retain appropriate width and thickness (usually the width is 6-10mm [165][166][167][168] ), and finally make the morphology of the remnant meniscus similar to that of NLM. 56,132,143 Partial meniscectomy is currently favored as the treatment for patients with symptomatic stable DLM.…”
Section: Methods and Choices Of Surgical Treatment Of Dlm And Its Les...mentioning
confidence: 99%